Korelasi Kadar Hemoglobin dan Hematokrit dengan Kadar Total Iron Binding Capacity (TIBC) pada Pasien Penyakit Ginjal Kronis - Lidyaningrum, Galuh Ajeng; Aliviameita, Andika (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : Chronic Kidney Failure (CKD) is a condition where the kidneys are structurally and functionally damaged characterized by a decrease in Glomerular Filtration Rate (GFR) reaching ≤ 60 ml/min/1.73m2 for more than three months. About 80 - 90% of patients with CKD experience anemia. AIMS : This research aims to determine the correlation of hemoglobin and hematocrit levels with Total Iron Binding Capacity (TIBC) levels in patients with chronic renal failure. METHOD : The research design used quantitative analysis with cross sectional method. The study used secondary data of as many as 55 respondents of chronic kidney disease patients undergoing hemodialysis. This study was conducted at the East Java Province Haji Hospital in March 2025. RESULT :  The normality test results showed that hemoglobin and hematocrit levels were not normally distributed (p < 0.05) while TIBC levels were normally distributed (p > 0.05). Kendall's tau b non-parametric correlation test there is no correlation between hemoglobin levels with TIBC (r = 0.134; p = 0.154), and hematocrit with TIBC levels (r = 0.172; p = 0.066). CONCLUSION : The results of this study showed no correlation between hemoglobin and hematocrit levels with total iron binding capacity (TIBC) levels in chronic kidney disease patients undergoing hemodialysis at Haji Provincial General Hospital of East Java .